Development of Multi Standard Information Technology Governance Audit Tool with SDLC Approach - Hermanto, Agus; Firmansyah, M. Syafrie (Information Technology and Science (ITScience), 2023)
In the era of digitalization, business organizations are competing to improve the quality of their services by utilizing information technology. Reliable information technology applications can be used to help the company's operations become better, while improper application of information technology can slow down the process. The process of establishing information technology through IT governance audits will optimize the application of information technology in a business. The implementation of an IT audit generates plenty of data that must be appropriately managed. Audits conducted using traditional systems frequently encounter issues such as difficulties maintaining audit indicator data, manually keeping of evidence at risk of getting damaged or lost, the process for generating reports is quite long, the audit monitoring operations are ineffective, and because there are numerous types of standards with different indicators, multiple tools are required while performing audits. In order to answer these issues, this study implemented a multi standard information technology governance audit tool that capable of managing audit activity data from many standards in a single system. The PHP and javascript programming languages, MySQL database, as well as the Laravel and VueJS Frameworks, will be used in the construction of this audit tool. The SDLC method was applied in this study, with numerous stages including planning to maintenance. Through blackbox testing on the various functions contained in the developed multi-standard audit tool, it is shown that the system can function as expected or intended. As well as through the usability testing questionnaire, it was concluded that the multi-standard audit tool developed had fulfilled the usability aspects.